Kinetic study of aza-amino acid incorporation into peptide chains: Influence of the steric effect of the side chain. (17th December 2022) - Härk, Heleri Heike; Troska, Alla; Arujõe, Meeli; Burk, Peeter; Järv, Jaak; Ploom, Anu
Abstract: Aza-peptides are peptidomimetics developed to avoid drawbacks connected with peptide instability in drugs. However, information concerning their bioactivity is quite limited due to the absence of efficient synthetic strategies to these compounds by SPPS (solid-phase peptide synthesis) method. Herein, we investigate, the effect of steric hindrance of various aza-amino acids (AzGly, AzAla, AzLeu, AzVal) on their reactivity with the N -terminus of amino acids in the synthesis of model aza-peptide H-AzAA-Ala-Phe-NH2 using BTC (Bis(trichloromethyl) carbonate) as an activator for aza-amino acid precursor. The results of kinetic measurements showed that this method could be used for aza-amino acid incorporation into peptide regardless of the structure of the preceding amino acid. However, for effective coupling of AzGly, DSC ( N, N ′-Disuccinimidyl carbonate) is the preferable activator. Graphical abstract: Image 1